Engenharia clínica aplicada à análise da variabilidade de parâmetros de referência para classificação da função pulmonar de adultos brasileiros - Silva, Paulo Roberto da (2016)
One of the basic applications of biomedical engineering refers to the testing of clinical use equipment, the assessment of its nature, accessibility and / or its features. In the evaluation of the respiratory system, are available different parameters of reference (PR) for the spirometry test, one of the main pulmonary function tests, which can measure: volumes, capacities and pulmonary flows. These PR based mainly on ethnic data, age and gender in healthy subjects, but with differences between populations studied, as in Brazil with its great diversity of races and ethnic groups, there may be misdiagnosis. Because of this, the objective of this study was to analyze in this population, three of the most used PR: PR-P (Pereira et al., 2007), PR-K (Knudson et al., 1983) and PR-Q (Quanjer et al., 2012). The procedure was a descriptive exploratory study with 683 subjects (180 men and 503 women) between 24 and 59 years, in good health, regular physical exercises practitioners with minimum frequency of twice a week. Anamnesis was applied, collected data of mass and height, performed forced spirometry (bidirectional spirometer - Care Fusion Microloop) and the following respiratory variables were measured, FEV1, FVC, PEF and FEF75. With the main results it was found that the average age was 42 years (male: 40.6 years; women: 44.4 years); BMI average of 26 kg / m² (male: 26.26 kg / m²; female: 26.44 kg / m²); and time the average physical exercises practice 52 months (male: 66.9 months; female: 37.9 months). When analyzing the variation of the reference parameters for pulmonary function classification between the three protocols tested, we found a statistically significant difference (p <0.05) between FVC, FEV1, PEF and FEF75 to the levels required and achieved in all PR, as well as restrictive and obstructive signs. For the PR-P, even with individuals with asymptomatic characteristics and practitioners of physical exercises, 17.2% of subjects were classified with some degree of restriction and 17.3% with obstruction, away from the PR-K and PR-Q which respectively had values for restrictive of 7.0% and 12.8% and for obstruction of 7.1% and 4.8%. We conclude that these PR may induce to errors, leading to different rating, where one individual can be considered in normal state, restrictive or obstructive, depending on the chosen protocol. It was identified that nutritional status interfere with respiratory function, demonstrating significant association between nutritional status and pulmonary function test for males, x² = 9.80 (p = 0.04). Thus, overweight men had 1.9 times more risk to have the insufficient lung function test, even practicing regular physical exercises. There was no significant association in any of the genres between the pulmonary function test and the time of physical activity. The Pearson correlation test confirmed the lack of correlation between the FEV1, FVC and PEF with practice time for both genders.